Rewilding through inappropriate species introduction: The case of European bison in Spain - Carlos Nores; Diego Álvarez‐Laó; Alberto Navarro; Francisco Javier Pérez‐Barbería; Pedro María Castaños; Jone Castaños de la Fuente; Arturo Morales Muñiz; Concepción Azorit; Joaquín Muñoz‐Cobo; Carlos Fernández Delgado; Carlos Granado Lorencio; Paul Palmqvist; et al. (Conservation Science and Practice)
Abstract Most European rewilding initiatives are based on the recovery of large herbivores, particularly European bison Bison bonasus, aiming at restoring ecosystem processes and increase trophic complexity. The growing support for the release of bison as a wild species, and change its legal status, in Spain, as an ecological analogue of the extinct steppe bison Bison priscus, makes it an excellent example to reflect the limits of a rewilding biogeographically advisable. We discuss if this initiative could be justified from ecological, biogeographical, ethical, and legal reasons. Besides remarkable taxonomic and functional differences between both bison species, the Mediterranean environment, under the present and future climatic scenarios, does not suit the European bison. Furthermore, there is no evidence to support the presumption that the European bison was ever present in the Iberian Peninsula, with legal implications. We expect that our approach will be inspirational for similar assessments on rewilding initiatives globally.